2001
DOI: 10.1046/j.1471-4159.2001.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of MARCKS and MARCKS‐related protein expression in BV‐2 microglial cells in response to lipopolysaccharide

Abstract: Myristoylated alanine-rich C kinase substrate (MARCKS) and MARCKS-related protein (MRP) have been implicated in membrane-cytoskeletal events underlying cell adhesion, migration, secretion, and phagocytosis. In BV-2 microglial cells, lipopolysaccharide (LPS) elicited a dose-dependent increase in mRNA of both MRP (sixfold) and MARCKS (threefold) with corresponding increases in [ 3 H]myristoylated and immunoreactive protein levels. LPS also produced signi®cant increases in protein kinase C (PKC)-b twofold and PKC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…Thus, our data on the paradoxical effects of PP1 and PP2 on decidual c-Src are novel and convincing, although molecular mechanisms underlying the paradoxical activation remain to be elucidated. Some studies have reported that PP1 does not act expectedly as a Src inhibitor when used for treatment of some cell types [29][30][31], and therefore there are several possibilities to explain our observation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, our data on the paradoxical effects of PP1 and PP2 on decidual c-Src are novel and convincing, although molecular mechanisms underlying the paradoxical activation remain to be elucidated. Some studies have reported that PP1 does not act expectedly as a Src inhibitor when used for treatment of some cell types [29][30][31], and therefore there are several possibilities to explain our observation.…”
Section: Discussionmentioning
confidence: 88%
“…Although herbimycin A has been widely used as a tyrosine kinase inhibitor with Src selectivity, several studies demonstrate that it behaves in a manner different from pyrazolo pyrimidine-type SFK inhibitors [31,40,41]. PP1 and PP2 act as competitive inhibitors of ATP for SFKs involving threonine 338 common in the kinase domain [9,10], which, however, has become controversial [42].…”
Section: Discussionmentioning
confidence: 99%
“…Since the activation of TRPV1 induces several phenomena, including the phosphorylation of TRPV1 itself (Tominaga and Tominaga 2005), the alteration of gene expression induced by capsaicin injection may reflect TRPV1 phosphorylation or downstream signaling. Many genes known to be up-regulated under activated nuclear factor-kappa B (NF kappaB) were detected to be up-regulated (Ccl19 (Pietilä et al 2007), Becn1 (Copetti et al 2009), Ccl2 (Ueda et al 1997), Ns5atp9 (Li et al 2008), Egr1 (Zheng et al 2009), Marcks (Sunohara et al 2001), Col1a1 and Col3a1 (Wu and Chakravarti 2007)). Genes which are upregulated under mammalian target of rapamycin (mTOR) were also up-regulated (Igf2 (Erbay et al 2003), Plp (Tyler et al 2009)).…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA level of myristoylated alanine-rich C kinase substrate (MARCKS) and MARCKSrelated protein (MRP) increase with the increase in protein kinase C (PKC). 14) Prior to iNOS induction, activation of nuclear factor kB (NFkB) is necessary. It is reported that LPS induces the release of a large amount of pro-IL-1b other than mature IL-1b, although the role of pro-IL-1b is unknown.…”
Section: Microglial Activation In Various Neuro-logical Diseasesmentioning
confidence: 99%